Epidemiologia molecular, fatores de risco e prognóstico da infecção por Enterococcus spp resistentes à vancomicina em situação de introdução recente: um estudo em dois hospitais públicos de Bauru-SP - Correa, Adriana Aparecida Feltrin [UNESP] (2014)
In the decades that preceded the emergence of vancomycin resistance, Enterococcus spp. were not considered pathogens of greatest risk for patients undergoing health care. These bacteria rarely caused systemic infections and were isolated mainly from urinary tracr infections. Presently, they are considered a major threat in hospitals due to the emergence of vancomycin-resistant Enterococci (VRE). Our study sought to provide a wide evaluation of the epidemiology, risk factors, clonality and outcome of VRE colonization/infection in two hospitals from a public health consortium: Hospital Estadual Bauru (HEB) and Hospital Estadual Manuel de Abreu (HEMA) Hospital , both belonging to São Paulo State Health Secretariat. We combined classic epidemiological methods and molecular epidemiology. The study period extended from January 2010 through June 2012 , corresponding to the time of emergence and spread of VRE in hospitals in the study. We included 122 subjects who acquired VRE in one of the study hospitals, and 8 cases classified as imported (i.e., who acquired VRE in other health services) . The isolates were obtained from clinical cultures (requested by attending physicians) or surveillance cultures (rectal swabs collected under the guidance of the Committee on Hospital Infection Control). VRE were characterized by the usual methods of species identification and antibiotic susceptibility. All isolates were subjected to molecular typing using Pulsed-Field Gel Electrophoresis (PFGE) using the restriction enzyme SmaI . Case-control studies (with multivariable analysis) were performed excluding subjects who acquired VRE in other services. For the remaining 122 cases , 244 controls were selected , in which VRE was not identified. Among the cases from the study hospitals, 113 (86.9%) were identified as Enterococcus faecium and 17 (13.1%) and Enterococcus faecalis. Overall, 88 (67.7%) were isolated in HEB and 42 (32.7%) in HEMA . The autochthony was ...